Food Waste in the Implementation of the Free Nutritious Meals (MBG) Program: From Nutrition to Emissions and Management Strategies - Priyaji Agung Pambudi; Savina Nurma Fardiani (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
The MBG program has reached 58.1 million beneficiaries, however, it also generates environmental impacts in the form of food waste. This study examinated food waste generation and management practices through a conceptual approach, field observations, and interviews with SPPG. The estimated food waste generated by the MBG program reaches 1.1-1.4 million tons per year at both SPPG and schools, with most waste remaining unmanaged and relying solely on landfill disposal. Open dumping landfills pose a significant risk of methane (CH4) emissions. Existing food waste management practices in the MBG program are estimated to produce annual emissions of approximately 47,600 metric tons of CH4 and 1,173.2 billion tons of CO2e, thereby incresing the burden on national emissions reduction targets. Emission prevention and environmental impact mitigation can be achieved through waste management infrastructure at SPPG or colectivelly at district and municipal levels. Ideal management practices include biocomposting (fertilizer production), biodigester (bioenergy production), and maggot cultivation (animal protein production). Through these approaches, the MBG program not only provides nutrition but also transforms waste into fertilizer, bioenergy, and protein, supporting low-carbon developmen initiativest.